2003
DOI: 10.1016/s0092-8674(03)00401-x
|View full text |Cite
|
Sign up to set email alerts
|

Rb-Mediated Heterochromatin Formation and Silencing of E2F Target Genes during Cellular Senescence

Abstract: Cellular senescence is an extremely stable form of cell cycle arrest that limits the proliferation of damaged cells and may act as a natural barrier to cancer progression. In this study, we describe a distinct heterochromatic structure that accumulates in senescent human fibroblasts, which we designated senescence-associated heterochromatic foci (SAHF). SAHF formation coincides with the recruitment of heterochromatin proteins and the retinoblastoma (Rb) tumor suppressor to E2F-responsive promoters and is assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

96
2,090
3
25

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 2,004 publications
(2,214 citation statements)
references
References 51 publications
96
2,090
3
25
Order By: Relevance
“…Inhibition of E2F transcription factors by Rb is an important pro‐senescence process (Mallette, Goumard, Gaumont‐Leclerc, Moiseeva & Ferbeyre, 2004; Narita et al., 2003; Sebastian, Malik, Thomas, Sage & Johnson, 2005). Our data support the view that plasma membrane depolarization promotes senescence through the Rb pathway, as repressed mitotic genes are known E2F targets and the inhibition of Rb prevents senescence induced by plasma membrane depolarization.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of E2F transcription factors by Rb is an important pro‐senescence process (Mallette, Goumard, Gaumont‐Leclerc, Moiseeva & Ferbeyre, 2004; Narita et al., 2003; Sebastian, Malik, Thomas, Sage & Johnson, 2005). Our data support the view that plasma membrane depolarization promotes senescence through the Rb pathway, as repressed mitotic genes are known E2F targets and the inhibition of Rb prevents senescence induced by plasma membrane depolarization.…”
Section: Discussionmentioning
confidence: 99%
“…This observation further confirms that nonphysiological modification of BRG1 expression triggers senescence. In fact, it has been shown that during senescence, distinct heterochromatin structures accumulate (Narita et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that distinct heterochromatin structures accumulate during senescence and could represent a hallmark of this process. In particular, Narita et al (2003) showed heterochromatin formation during cellular senescence and showed that DNA from senescent cells was more resistant to limited micrococcal nuclease digestion when compared with that from normal cells. In our experimental model, cells with silenced BRG1 showed increased resistance to nuclease digestion when compared with controls ( Figure 4a).…”
Section: Senescence Is Associated With Changes In Chromatin Statusmentioning
confidence: 99%
“…This arrest serves to allow time for repair of DNA damage, which may then result in resumption of proliferation or, if the damage is too severe, permanent arrest (Linke et al, 1996) or senescence (Narita et al, 2003) to prevent further genetic instability (Almasan et al, 1995a;Bindra and Glazer, 2005;. Although this mechanism is beneficial to non-neoplastic tissues, in (Table 1) using the primers described in Table 2 (Materials and methods) at various time points following irradiation.…”
Section: Discussionmentioning
confidence: 99%